Quasi-static and dynamic testing of splitting, expansion and expansion-splitting hybrid tubes under oblique loading. (February 2017) - Moreno, C.; Beaumont, R.; Hughes, D.J.; Williams, T.; Dashwood, R.
Highlights: Quasi-static and dynamic testing was performed on splitting, expansion and hybrid expansion-splitting tubes. 'Flat topped' energy absorbers, such as splitting, expansion and expansion-splitting tubes, increase their mean load as they are subjected to oblique loading. A novel methodology is proposed to assess the sensitivity of Type I, 'flat topped' energy absorbers to the application of oblique loading. Expansion-splitting tubes exhibit little sensitivity to the application of oblique loading under quasi-static conditions. Splitting tubes and Expansion-splitting tubes exhibit little sensitivity to the application of oblique loading under dynamic conditions. Abstract: Railway vehicles energy absorbers are required to comply with the BS EN 15227. These standards require the energy absorbers to dissipate the collision energy while preventing overriding, which implies resisting any vertical loads during the collision. Unlike crumple columns, 'flat topped' energy absorbers exhibit an increased axial mean load under oblique loading conditions, instead of decreasing their energy absorption capacity when subjected to a critical transverse loading. A newly proposed methodology of assessing the oblique loading performance of 'flat topped' is presented here to compare the performance of the splitting, expansion and the novel expansion-splitting tubes (all 'flat topped' energy absorbers). The methodology comprises the comparison of the measured axial mean load between purely axial tests and oblique loading tests, to assess the sensitivity of the tubes to the oblique loading. Dimensionally scaled tubes, compressed by expansion, splitting and expansion splitting dies, were quasi-statically and dynamically tested against 5° and 10° inclined plates to reproduce the oblique loading conditions. The quasi-static results showed that the expansion-splitting tubes, unlike splitting and expansion, were largely insensitive to the application of a transverse loading. Therefore, the expansion-splitting tubes could be regarded as more efficient than expansion or splitting tubes under quasi-static oblique loading. The dynamic results showed that the splitting tubes became as insensitive as the expansion-splitting tubes to the application of a transverse loading.